The Influence of Technology Acceptance Model on Service Level Agreement Through Actual System Use in Last-Mile Logistics Operations - Haris Fitriadi; Maniah Maniah; Melia Eka Lestiani (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study examines the influence of Technology Acceptance Model (TAM) on Service Level Agreement (SLA) achievement through Actual System Use in last-mile logistics operations at SiCepat Ekspres. Utilizing a quantitative approach and variance-based structural equation modeling (PLS-SEM), data were collected from 278 operational employees. Six TAM constructs Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Trust, Perceived Risk, Organizational Readiness, and Social Influence were examined as independent variables, with Actual System Use as mediating variable and SLA as the dependent variable. Results reveal that Social Influence is the strongest predictor of Actual System Use (β = 0.420), while Actual System Use significantly drives SLA achievement (β = 0.585). The model explains 75.5% of SLA variance, underscoring the central role of actual technology use as a strategic mediator in the TAM–SLA relationship within last-mile logistics operations.